Therapeutic Communication In Reducing The Levels Of Famillies Anxiety Whose Child Were Hospitalitation - Tutik Setyowati; Teguh Wahyudi; Sutarmi Sutarmi (Poltekkes Kemenkes Semarang, 2014)
This study aims to explain the relationship between therapeutic communication done by nurses and the anxiety of family members of hospitalized child who are suffering from infectious diseases. A total of 44 respondents were included in this study using purposive sampling technique. The data were taken using a questionnaire on therapeutic communication and anxiety with a closed question types. The data then were processed using Kendal tau statistical tests with 95% significance level. The results of the analysis shows that 75 % of respondents experienced minor anxiety, 13.6 % had moderate anxiety, and 11.4 % had severe anxiety. Data on therapeutic communication indicates that 9.1 % of nurses less communicate, 52.3 % make enough communication, and 36.6 % make a good communication. Correlation analysis using Kendal tau technique shows that there is a relationship between therapeutic communication done by a nurse and the degree of anxiety experienced by families whose child are being hospitalized with infectious diseases (ä = -0.34 , p = 0.018 ). Nurses should always apply the principles of therapeutic communication to communicate with patients because it can minimize the stress and improve the process of adaptation to stress.